Complete Resolution of Pseudomalignant Erosion in a Reflux Gastroesophageal Polyp with Proton Pump Inhibitor - Takahiko Nakajima; Haruo Yagi; Hayato Baba; Takashi Minamisaka; Shigeharu Miwa; Shinichi Hayashi; Takeshi Nishida; Hideki Hatta; Koichi Tsuneyama; Johji Imura (Hindawi Limited, 2015)
Pseudomalignant erosion is a diagnostic pitfall for pathologists in the differential diagnosis of malignant neoplasms. Here, we present a challenging case of a biopsy specimen from the eroded head of a polyp at the esophagogastric junction. A malignant neoplasm could not be ruled out due to the presence of bizarre stromal cells. A second biopsy performed after the administration of a proton pump inhibitor (PPI) for 4 weeks revealed endoscopic resolution of the polyp along with the complete histological resolution of the bizarre stromal cells and led to the diagnosis of pseudomalignant erosion in a reflux gastroesophageal polyp. In conclusion, histological and endoscopic response to PPI therapy is an important clue for the correct diagnosis of reflux gastroesophageal polyps with pseudomalignant erosion.